An Innovative Nitrate Pollution Index and Multivariate Statistical Investigations of Groundwater Chemical Quality of Umm Rijam Aquifer (B4), North Yarmouk River Basin, Jordan - Obeidat, Mutewekil M.; Awawdeh, Muheeb; Al-Rub, Fahmi Abu; Al-Ajlouni, Ahmad (IntechOpen, 2012)
None